2002
DOI: 10.1053/jhep.2002.34745
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E-ε4 protects against severe liver disease caused by hepatitis C virus

Abstract: The outcome of infection with hepatitis C virus (HCV) varies greatly. The virus associates with serum lipoproteins, including those containing apolipoprotein E (apoE) and apolipoprotein B (apoB), and may enter cells via the low-density lipoprotein receptor (LDLR). ApoE genotypes can affect the extent of damage in diseases caused by 2 other virusesherpes simplex virus type 1 (HSV1; in Alzheimer's disease and herpes labialis) and human immunodeficiency virus (HIV). We therefore investigated whether specific apoE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
134
2
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(149 citation statements)
references
References 30 publications
8
134
2
5
Order By: Relevance
“…The advantage for HCV to use a host protein for its cell entry is to mask the host immune response so that it can establish a persistent infection. This concept is supported by recent findings derived from genetic studies that the outcome of HCV infection correlated with apoE polymorphism (44,60). The apoE3 allele was found to correlate with persistent HCV infection (44), whereas the apoE2 and apoE4 alleles were associated with a reduced likelihood of chronic HCV infection (44,60).…”
Section: Vol 81 2007 Requirement Of Apoe For Hcv Infectivity and Prsupporting
confidence: 57%
“…The advantage for HCV to use a host protein for its cell entry is to mask the host immune response so that it can establish a persistent infection. This concept is supported by recent findings derived from genetic studies that the outcome of HCV infection correlated with apoE polymorphism (44,60). The apoE3 allele was found to correlate with persistent HCV infection (44), whereas the apoE2 and apoE4 alleles were associated with a reduced likelihood of chronic HCV infection (44,60).…”
Section: Vol 81 2007 Requirement Of Apoe For Hcv Infectivity and Prsupporting
confidence: 57%
“…We reported that HCV also binds to extracellular sApoE and found that both sApoE protein concentration and variant type affect virus infectivity. For example, sApoE4 caused a reduction in HCV infectivity, a finding that is consistent with clinical data indicating that the ApoE4 genotype is associated with a degree of resistance against HCV infection (48,49). During the preparation of the manuscript, another similar result was also reported (50).…”
Section: Discussionsupporting
confidence: 83%
“…NO is critical for synapses [100][101][102][103] (b) Increasing cholesterol availability to the developing brain, cholesterol as a glial synaptogenic factor and indirect trigger for myelination in the brain [34,104,28,105,27] Infection (a) ApoE4 by downregulating LDL receptors may starve enteric pathogens from cholesterol and block proliferation. The LDL-receptor pathway is also highly conserved across the animal kingdom [106][107][108][109][110] (b) ApoE is secreted in a polarized manner by enterocytes, increased by 25-OHcholesterol and decreased by LPS through an LXR α /RXR independent signaling pathway [47].…”
Section: Boxmentioning
confidence: 99%